Variasi Pengaturan Tempat Duduk dalam Pembelajaran di Kelas III Sekolah MIS Al-Mubarakah Mohiyolo - Sri Wahyuni Yusuf; Yurni Rahman (Pusat Riset dan Inovasi Nasional, 2025)
This study originates from the issue of limited variation in seating arrangements in Grade III of MIS Al-Mubarakah Mohiyolo, where the conventional formation has predominantly been used. Such conditions have led to low levels of motivation, engagement, and interaction among students during the learning process. The purpose of this research is to describe the variations of seating arrangements applied by teachers and to analyze their implications for teaching and learning dynamics. This research employed a qualitative descriptive method with a case study design. Data were collected through observation, interviews, and documentation, and were analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that teachers implemented three types of seating arrangements: traditional formation, U-shaped formation, and conference formation. Among these, the U-shaped formation was perceived as the most effective by students, as it enhances visibility, facilitates mobility, strengthens interaction between teachers and students as well as among students, and is adaptable for both individual and group learning. These findings highlight that innovative seating arrangements can serve as an effective classroom management strategy to foster a conducive learning environment, improve student motivation, and support the achievement of learning objectives.